Pengaruh Model Pembelajaran E-Learning Berbantuan Aplikasi Kahoot terhadap Hasil Belajar Siswa SMA - Wolfgang Asindo Seran; Stefania Sonia Manek; Ivony Sarlin Asa (Lembaga Pengembangan Kinerja Dosen, 2024)
This research is motivated by the gap between the demands of the digital era on cutting-edge geography and the geography learning process at SMA Plus St. Albertus Agung Weleun, Malaka Regency. The learning process tends to be verbal and teacher-centered, the use of media with cutting-edge technology is still lacking in attention so that educators have minimal or lack of variation in using learning models and media. This has an impact on learning that is often boring and this condition affects student learning outcomes which are not yet satisfactory, which is the problem of this research. This study aims to determine: 1) the effect of the e-learning learning model assisted by the Kahoot application on student learning outcomes at SMA Plus St. Albertus Agung Weleun; 2) the difference in the effectiveness of the e-learning learning model assisted by the Kahoot application on student learning outcomes at SMA Plus St. Albertus Agung Weleun. This research is a quasi-experimental study with a Nonequivalent-Group Pretest-Posttest Design. The sample in this study were students in grades XA and XB where class XA was the experimental class and class XB was the control class. The data collection technique was carried out using a test instrument consisting of a pretest and posttest developed based on teaching materials. The instrument has met the requirements for validity and reliability. The difference in learning outcomes between the control group and the experimental group was analyzed using the T-test, while in this study it was the independent sample t-test and the n-gain score test. The various analysis techniques were analyzed using SPSS version 24.00. The results of the study showed that: 1) there is a significant effect of the e-learning learning model assisted by the Kahoot application on the learning outcomes of students at SMA Plus St. Albertus Agung Weleun with a sig value (2-tailed) of 0.000 ≤ 0.05. 2) the e-learning learning model assisted by the Kahoot application is less effective in improving student learning outcomes, the experimental class value is 54.9550 and the control class using conventional methods is not effective in improving student learning outcomes, the value is 15.1133.